THE EFFECT OF LEARNING STYLES AND MOTIVATION ON INDONESIAN STUDENTS’ ENGLISH ACHIEVEMENT - Hery Yufrizal; . Sudirman; Basturi Hasan (Indonesian EFL Journal, 2015)
This research aims to find out whether there is any significant interaction between motivation and learning style on students’ English achievement in Bandar Lampung. This research is a non-experimental study with variant analysis study. The research involves 430 students of Science Department, Faculty of Teaching and Education, University of Lampung, Indonesia. Data were taken by giving a set of test in which validity and reliability are tested. Data for motivation and learning styles were taken from students’ reponses to multiple choice questionnaire each consisting of 40 questions. The results of the analysis show that there is no significant interaction between motivation and learning styles on students’ English Achievement. This means that the combination of motivation and learning styles cannot distinguish between high achiever students and the lower ones. Learning styles have significant influence on students’ English achievement. Students with different learning styles have different English achievement. Motivation does not have significant effect on students’ English achievement. Students with different motivation did not have different result of English achievement.Keywords: motivation, learning styles, English achievement.